Histopathological and Hematological Assessment of Bone Marrow Metastasis in Breast Cancer Patients, A Cross-Section Clinical Study - Ikram Ul Haq, Maliha Asif, Syed Naveed Haider, Abuzar Ghaffari, Mansoor Latif, Fatima Jannat, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Bone marrow metastasis in breast cancer patients may result in major hematological abnormalities and is underdiagnosed. In an attempt to prevent metastases from being diagnosed in a late stage, this study seeks to evaluate the histopathological and hematological changes that occur with such metastases. Methodology: An approval for conducting this cross-sectional clinical study was received through the IRB from tertiary care hospitals in Pakistan, from January 2022 to December 2022. Eighty female patients with histologically confirmed breast cancer and clinical suspicion of metastasis were included. Posterior iliac crest bone marrow aspiration and trephine biopsies were done. CBC, reticulocyte count, ESR, and LDH were recorded. H&E staining was performed for histopathological analysis, and cytokeratin AE1/AE3, GCDFP-15, ER/PR immunostaining was done to confirm metastatic involvement. Statistical significance was set at p < 0.05, and data analysis was performed using SPSS version 25. Results: Bone marrow metastasis was shown in 26 (32.5%) out of 80 breast cancer patients. Hemoglobin (8.9 g/dL), platelet (104 × 10⁹/L), and WBC counts (3.2 × 10⁹/L) in these patients were significantly lower than in non-metastatic cases (p < 0.001). The metastatic group also showed elevated ESR and LDH levels. Histology showed clusters of malignant epithelial cells that were positive for cytokeratin AE1/AE3 and GCDFP-15. Marrow infiltration was strongly associated with pancytopenia. Conclusion: Breast cancer bone marrow metastasis is a major negative prognostic indicator, presenting with characteristic hematological abnormalities. Early histopathological and hematological assessment is necessary for early diagnosis and timely treatment planning. Keywords: Breast cancer, Bone Marrow, Metastasis, Histopathological, Hematological